Mechanism of nanomaterial-induced lipid droplet formation in Raphidocelis subcapitata is mediated by charge properties - McKeel, Emma; Kim, Hye-In; Jeon, Su-Ji; McKinnon, Britta; Giraldo, Juan Pablo; Klaper, Rebecca (Frontiers in Plant Science, 2025)
Increasing the production of renewable energy will be critical to achieving global sustainability goals in the coming decades. Biofuels derived from microalgae have great potential to contribute to this production. However, cultivating algae with sufficient neutral lipid content, while maintaining high growth rates, is a continual challenge in making algal-derived biofuels a reality. Previous work has shown that exposure to polymer-functionalized carbon dots can increase the lipid content of the microalgae Raphidocelis subcapitata. This study investigates this finding, aiming to determine the mechanisms underlying this effect and if altering nanoparticle surface charge mediates the mechanism of action of the carbon dots used. Carbon dots with both negative and positive surface charges were added to microalgal cultures, and the impacts of this exposure were analyzed using high-content imaging, growth measurements, and chlorophyll content measurements. Results indicate that positively charged carbon dots induce a nano-specific increase in lipid content but also cause decreases in growth. Additionally, the mechanism of action of each nanoparticle was examined by conducting a morphological comparison to treatments with known mechanisms of action. This analysis showed that negatively charged carbon dots cause similar impacts to R. subcapitata as nitrogen deprivation. Nitrogen deprivation is known to increase lipid content in microalgae. The findings of this study suggest that carbon dots may have surface charge dependent effects on the lipid metabolism of R. subcapitata. Future work should consider the use of carbon dots with varied surface charge densities for enhancing algae biofuel production in bioreactors.